2009
DOI: 10.1111/j.1742-4658.2009.07023.x
|View full text |Cite
|
Sign up to set email alerts
|

The endogenous retinoid metabolite S‐4‐oxo‐9‐cis‐13,14‐dihydro‐retinoic acid activates retinoic acid receptor signalling both in vitro and in vivo

Abstract: Retinoic acid receptor (RAR) and retinoid X receptor are ligand-induced transcription factors that belong to the nuclear receptor family. The receptors are activated by small hydrophobic compounds, such as all-trans-retinoic acid and 9-cis-retinoic acid, respectively. Interestingly, these receptors are also targets for a number of exogenous compounds. In this study, we characterized the biological activity of the 9-cissubstituted retinoic acid metabolite, S-4-oxo-9-cis-13,14-dihydro-retinoic acid (S-4o9cDH-RA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The endogenous levels of S-4o9cDH-RA were found to be higher than those of all-trans RA in mice and rats, and the compound is able to activate transcription of RAR target genes [120]. In vivo, S-4o9cDH-RA induces morphological changes in the chicken wing bud similar to those induced by all-trans RA [120]. Additional RAR ligands include b-cryptoxanthin and lutein, which act as RAR ligands in a yeast two-hybrid system and bind RA with lower affinity than all-trans RA [121].…”
Section: Retinoid Receptor Ligandsmentioning
confidence: 95%
See 2 more Smart Citations
“…The endogenous levels of S-4o9cDH-RA were found to be higher than those of all-trans RA in mice and rats, and the compound is able to activate transcription of RAR target genes [120]. In vivo, S-4o9cDH-RA induces morphological changes in the chicken wing bud similar to those induced by all-trans RA [120]. Additional RAR ligands include b-cryptoxanthin and lutein, which act as RAR ligands in a yeast two-hybrid system and bind RA with lower affinity than all-trans RA [121].…”
Section: Retinoid Receptor Ligandsmentioning
confidence: 95%
“…The retinol metabolite 14-hydroxy-4,14-retro retinol was also shown to be active in vivo [10]. Another recently identified and characterized retinoid is the 9-cis-substituted RA metabolite S-4-oxo-9-cis-13,14-dihydro-RA (S-4o9cDH-RA) [120]. The endogenous levels of S-4o9cDH-RA were found to be higher than those of all-trans RA in mice and rats, and the compound is able to activate transcription of RAR target genes [120].…”
Section: Retinoid Receptor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies led to the discovery of several retinoids with potential biological activity, but only a few enzymes have been identified that could produce them in vivo (Buck et al, 1991;Heyman et al, 1992;Schuchardt et al, 2009). We originally identified and characterized the enzyme known as retinol saturase (RetSat) that catalyzes the saturation of all-trans-retinol (atROL) through a stereospecific reaction that generates (R)-all-trans-13,14-dihydroretinol [(R)-DROL] (Moise et al, 2004(Moise et al, , 2007(Moise et al, , 2008.…”
mentioning
confidence: 99%
“…Oxidized metabolites of RA. RA is metabolized by cytochrome P450 enzymes and its oxidized metabolites also activate RAR [141, 142]; however, the function of these RA derivatives in adipose tissue has not been reported.…”
Section: Intra/paracrine Effects Of Retinoic Acid Production From Vitmentioning
confidence: 99%